Efficacy and safety of upadacitinib in the treatment of recalcitrant vitiligo - Khondker, Lubna; Khan, M. Alauddin; Nabila, Noshin; Dash, Pranam Swapan; Nasrin, Tanjina; Hasan, M. Kamrul; Nath, Pankaj Kanti (International Journal of Research in Medical Sciences, 2025)
Background: Vitiligo is an acquired autoimmune disease resulting in depigmented patches of the skin, often leading to a significant psychosocial burden on patients. Building on recent advancements in understanding the immunological mechanisms in vitiligo pathogenesis, various potential treatment options such as JAK inhibitors are being clinically researched for vitiligo. In this study, upadacitinib was evaluated for its effectiveness and safety in treating recalcitrant vitiligo patients. Methods: This study was a prospective randomized clinical trial, thirty patients of group A were treated with Upadacitinib, a dose of 15 mg once daily for 16 weeks. Thirty patients of group B were treated with low dose oral prednisolone (0.3 mg/kg body weight) daily for 16 weeks and the severity of vitiligo was measured using the Vitiligo Area Severity Index (VASI). Results: The study shows that in Group A, the mean reduction of VASI score was lower in segmental vitiligo (1.24±0.43) and higher in acrofacial vitiligo (4.21±1.30). On the other hand, in Group B, the mean reduction of VASI score was almost similar in acrofacial vitiligo (2.17±0.35) and generalized vitiligo (2.23±0.44). The association between type of vitiligo and change in VASI score in Group A was statistically significant (0.002). At month 4, the VASI score was lower in group A (5.70±3.61) compared to group B (8.61±3.43), which was statistically significant (p=0.006). Conclusions: The observed repigmentation with minor adverse effects in all vitiligo patients with upadacitinib suggests that upadacitinib could be a promising therapeutic option for this challenging condition.